2019
DOI: 10.18332/tpc/111130
|View full text |Cite
|
Sign up to set email alerts
|

Did the introduction of pictorial health warnings increase information seeking for smoking cessation?: Time-series analysis of Google Trends data in six countries

Abstract: INTRODUCTION Pictorial health warnings (PHW) can influence smoking cessation rates and precursors thereof. However, both the magnitude and duration of their impact, in national populations, remain uncertain because of limitations of the available data. In this study we used Google Trends data from six European countries to evaluate whether the implementation of PHW was followed by a short-term increase in online searches on smoking cessation. METHODS We applied an interrupted time-series design using ARIMA mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
6
1
2
Order By: Relevance
“…Hence, it explained the fear and reluctance among our participants in seeking PHW understanding from their parents. Unfortunately, unlike findings from a study in Europe where a temporary surge of information-seeking over the internet following the introduction of new PHWs [50] was seen, most of our participants reported not attempting to seek further understanding of PHWs, even via the internet. A shocking discovery, considering the increasing pattern in seeking health information via the internet worldwide, including Malaysia [51].…”
Section: Discussioncontrasting
confidence: 99%
“…Hence, it explained the fear and reluctance among our participants in seeking PHW understanding from their parents. Unfortunately, unlike findings from a study in Europe where a temporary surge of information-seeking over the internet following the introduction of new PHWs [50] was seen, most of our participants reported not attempting to seek further understanding of PHWs, even via the internet. A shocking discovery, considering the increasing pattern in seeking health information via the internet worldwide, including Malaysia [51].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study across six European countries, France and the UK showed a short-term increase in RSV for smoking cessation terms, which however were not significant and were present only during the initial months. Ireland, Norway, Denmark, and Switzerland showed no increase in online searches (Kunst et al 2019).…”
Section: Tobacco and Other Nicotine Delivery Systemsmentioning
confidence: 87%
“…7 Nesse sentido, o estudo em questão indica que o Google Trends merece ser aprofundado quanto ao seu eventual potencial de complementar o monitoramento dessa epidemia de forma a conseguir capturar, sem ter que esperar a periodicidade das pesquisas epidemiológicas e posterior divulgação dos seus resultados, as mudanças constantes no modus operandi da indústria do tabaco. 7,14 O Google Trends tem sido, inclusive, utilizado em outros países [15][16][17] para medir a mudança de comportamento do usuário a partir de mudanças legislativas, econômicas e/ou educacionais voltadas ao combate de produtos derivados do tabaco ou a partir da reação de marketing da indústria a tais medidas. [15][16][17] Tal mudança pode ser expressa tanto pela busca de informação sobre cessação do uso [15][16][17] quanto pela substituição por um outro produto que permita a manutenção da dependência à nicotina, destacando-se os dispositivos eletrônicos para fumar.…”
Section: Discussionunclassified
“…7,14 O Google Trends tem sido, inclusive, utilizado em outros países [15][16][17] para medir a mudança de comportamento do usuário a partir de mudanças legislativas, econômicas e/ou educacionais voltadas ao combate de produtos derivados do tabaco ou a partir da reação de marketing da indústria a tais medidas. [15][16][17] Tal mudança pode ser expressa tanto pela busca de informação sobre cessação do uso [15][16][17] quanto pela substituição por um outro produto que permita a manutenção da dependência à nicotina, destacando-se os dispositivos eletrônicos para fumar. 18 Ademais, o Google Trends foi utilizado para entender como eventos imprevisíveis e agudos, como a epidemia de covid-19, podem…”
Section: Discussionunclassified